Antagonistic effects of some commonly used herbs on the efficacy of Artemisinin derivatives in the treatment of malaria in experimental mice - Idowu, O. A. (2023)
At the end the sixth day, Mm root extract, ML and Va leaf extract reduced parasitaemia by 86.83%, 84.20% and 48.10%, respectively (p < 0.05). A total parasite clearance (100% chemosuppression) was observed in the group treated with artesunate and chloroquine. However, the combination of each extracts of M. lucida, M. morindiodes and V. amygdalina with artesunate significantly reduced the chemosuppression to 89.93%, 89.43% and 86.93%, respectively.